COVID-19 Preparedness and Response: Validation of a Rapid Assessment Tool to Evaluate Priorities of Health Workers at the Grassroots Level - Bach Xuan Tran; Bach Xuan Tran; Chi Linh Hoang; Nguyen Thao Thi Nguyen; Huong Thi Le; Hai Quang Pham; Hai Quang Pham; Men Thi Hoang; Men Thi Hoang; Tu Huu Nguyen; Carl A. Latkin; Cyrus S. H. Ho; et al. (Frontiers Media S.A., 2021)
Since the initial phases of the COVID-19 outbreak, international recommendations for disease control have been readily available. However, blind implementation of these recommendations without grassroot-level support could result in public distrust and low adherence. This study evaluated the use of a public health priorities survey to rapidly assess perceptions of local health workers. A cross-sectional study using a web-based survey was conducted among 5,847 health workers and medical students from January to February 2020 to evaluate the level of prioritization of various public health measures. Measures with the highest levels of prioritization were "Early prevention, environmental sanitation, and improvement of population health" and "Mobilization of community participation in disease control," which were concordant with policies implemented by the Vietnamese government. This study also demonstrated a high level of internal validity among survey items and shared ranking of priorities among all occupational groups. The use of this public health priorities survey was found to be effective in identifying priorities as identified by grassroots health workers to provide real-time feedback to the national government. However, future iterations of this survey should consider limiting the use of each prioritization score to ensure that responses represent the reality of source limitations and consider focusing on medical professionals and community workers due medical students' limited experience with Vietnam's healthcare infrastructure.